A desiccation compound as a biofilm- and necrosis-removing agent: a case series. (2nd October 2022) - Cogo, Alberto; Bignozzi, A Carlo; Hermans, Michel HE; Quint, Bert J; Snels, Johannes Petrus; Schultz, Gregory
Abstract : Objective: A new compound, Debrichem (DEBx Medical BV, the Netherlands), a topical desiccation agent (TDA), is an active gel that contains an acidic species with a potent hygroscopic action. When in contact with microorganisms and necrosis, rapid desiccation and carbonisation of the proteins in these microorganisms, as well as of the extracellular matrix of biofilms and necrosis, occurs. The resulting 'precipitate' rapidly dislodges from the wound bed, resulting in a clean wound which granulates, which is a prerequisite for healing by secondary intention. Method: In a retrospective study, a series of mostly large and hard-to-heal lesions of different aetiologies were treated with a one-time application of the TDA, followed by weekly dressing changes. Results: Of the total of 54 lesions included in this case series, 22 were diagnosed as venous leg ulcers (VLUs), 20 as diabetic foot ulcers (DFUs), nine as post-traumatic, hard-to-heal lesions, two as vascular ulcers and one as an ischaemic ulcer. All of the VLUs, 75% of the DFUs and all of the other lesions reached complete granulation. Conclusion: The use of a TDA may contribute to the consistent, fast and easy removal of both biofilms and necrosis, and hence to wound healing.